High Performance Work Systems and Employee Outcomes in Indian Call Centres: A Mediation Approach - Ananthram, Subra; Xerri, M.; Teo, S.; Connell, J. (Emerald, 2018)
Purpose: The purpose of this paper is to empirically examine the relationships between high-performance work systems (HPWSs) and four employee outcomes – job satisfaction, employee engagement, presenteeism and well-being – in Indian call centres. Design/methodology/approach: A path model is developed to investigate the direct and mediation effects between the assessed variables. The study utilised a survey of 250 call centre employees working in five business process management firms based in India. Findings: The findings indicate that HPWSs have a positive relationship with job satisfaction, engagement and well-being. Job satisfaction also had a positive relationship with engagement and presenteeism, and engagement was positively related to presenteeism and well-being. However, there was no significant direct effect of HPWS on presenteeism. Mediation analysis showed that HPWS has an indirect effect on well-being via engagement and also via job satisfaction and engagement combined. Research limitations/implications: HPWS significantly increases job satisfaction and employee engagement and indirectly influences employee well-being via these outcomes. However, job satisfaction and employee engagement was also found to increase presenteeism, which, in turn, can reduce employee well-being. These findings contribute to the HPWS theory and the literature on employee well-being, and have implications for HR personnel and call centre management. Originality/value: Given the well-established challenges with employee retention in Indian call centre environments, one solution may be the adoption of a more strategic approach to HRM using HPWS. Such an approach may enhance employees’ perceptions that HPWS practices would have a positive influence on job satisfaction, employee engagement and employee well-being.